2004
DOI: 10.1002/adfm.200305111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structure of MCM‐41 Samples with a High Copper Content

Abstract: A series of MCM‐41s with a high copper content were synthesized at room temperature from sodium metasilicate (Na2SiO3) as the silicon source, tetraamminecopper(II) nitrate [Cu(NH3)4(NO3)2] as the copper source and cetyltrimethylammonium bromide (CTABr) as the template. The resulting material was characterized by using the following characterization techniques: X‐ray diffraction (XRD), N2‐adsorption isotherms, high‐resolution transmission electron microscopy (HRTEM), inductively coupled plasma (ICP), temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 30 publications
8
28
0
1
Order By: Relevance
“…The atomic weight of vanadium and iron were also greater than that of silicon, and which caused the increase of the reduced mass ( ). Hence, the vibration frequencies according to the formula = 1/2 c √ k/ decreased, and a similar phenomenon was observed and discussed by Kong et al 34 All these results suggested, in some extent, that the heteroatoms have been incorporated into the framework of SBA-15.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The atomic weight of vanadium and iron were also greater than that of silicon, and which caused the increase of the reduced mass ( ). Hence, the vibration frequencies according to the formula = 1/2 c √ k/ decreased, and a similar phenomenon was observed and discussed by Kong et al 34 All these results suggested, in some extent, that the heteroatoms have been incorporated into the framework of SBA-15.…”
Section: Resultssupporting
confidence: 76%
“…were used to estimate the incorporation of guest atoms in the mesoporous materials. 34 Some structure parameters of the samples were summarized in Table I. The increase of a 0 and D values could be taken as indication of the incorporation of the metals in the silica framework, probably due to the larger ion radii of V 5+ and Fe 3+ than that of Si 4+ .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, according to the literature, copper might be in strong interaction with the support as Cu-O-Si species which could explain both the green color of the sample and the absence of diffraction peaks [20,44,45,[54][55][56][57]. This result is supported by the Cu-X-ray mapping (figure 4 B) which shows a homogeneous distribution of copper on the support at the micrometric scale.…”
Section: Characterization Of the Adsorbentssupporting
confidence: 72%
“…Owing to a narrow and uniform pore size distribution, Ti-MCM-41-M393 has a smaller average pore size (28.6Å) and a higher surface area (896 m 2 /g) than any other Ti-MCM-41-M samples listed in Table 1. [30,31]. The band at 450 cm −1 is attributed to tetrahedral bending vibration of Si-O-Si bonds.…”
Section: N 2 Adsorption-desorption Isothermsmentioning
confidence: 96%